A cross-cultural approach to understanding entrepreneurial intention - Moriano, Juan A; Gorgievski, Marjan; Laguna, Mariola; Stephan, Ute; Zarafshani, Kiumars (Journal of career development, 2012)
The current research aims to shed light on the role of culture in the formation of career intentions. It draws on the Theory of Planned Behavior (TPB; Ajzen), which has been widely employed to predict intentions, including entrepreneurial career intentions, but past research has almost exclusively been conducted in “Western” countries. The current research specifically explores the extent to which both the strength of relationships of TPB predictors with entrepreneurial career intentions and the TPB predictors themselves are invariant across cultures. The study compares six very different countries (Germany, India, Iran, Poland, Spain, and the Netherlands), drawing on an overall sample of 1,074 students and their assessments of entrepreneurial career intentions. Results support culture universal effects of attitudes and perceived behavioral control (self-efficacy) on entrepreneurial career intentions but cultural variation in the effects of subjective norm.